The Relationships Between Illusory Truth Effect, Metacognitive Awareness And Working Memory Among Young Adults In Penang: The Role Of Processing Fluency - Mak, Chan Wai (2023)
The truth effect can be problematic in the information age if false information is shared repeatedly online. According to the dual process theory, cognition is divided into system 1 and 2. System 1 is automatic and unconscious, conversely, system 2 is deliberate and conscious. The truth effect is also known to be associated with processing fluency, which is the ease of how an item is processed. An item which is relatively more fluent in processing would engage system 1. Repeated items are more fluently processed, which in turn are perceived as true compared to non-repeated items that are relatively low in processing fluency. The aim of the current study was to investigate the relationship between working memory, metacognitive awareness, and the truth effect. It also aims to understand if processing fluency mediated each variable with the truth effect. In the current study, system 2 was represented by metacognitive awareness and working memory. Metacognitive awareness is the awareness and regulation of one’s mental process. Working memory is the ability to simultaneously store and process information in higher-order cognitive activities such as navigating a map, giving a presentation, and calculating a budget without a calculator or paper and pencil. The study was initially designed to be completed in a face-to-face, physical administration, but due to the Covid-19 nationwide lockdown, it was converted into an online administration.